Security measurement in Skaraborg 1998 - Eriksson, Bo G; Gustavsson (student), Jennie; Kristoffersson (student), Frida; Norlin (student), Marie-Louise (University of Gothenburg, 2006)
Security measurement in Skaraborg 1998 is a student essay (c level) in social psychology conducted at Skövde University. The data material has been made available with the approval of supervisor Bo Eriksson, University of Gothenburg.

The survey has been conducted in cooperation with the County Police Office in Skaraborg and Skaraborg County Council, and aims to serve as a basis for the police in its work to reduce crime and increase security in the project "Allas vårt ansvar". Data content includes information on perceived safety in the municipality, measures to increase personal safety, perceived crime and perceived security for the police.

Purpose:

The purpose of the study is to provide a picture of people's level of safety and an idea of ​​what affects the level of safety and to serve as a basis for the police's practical work.

Trygghetsmätning i Skaraborg är en studentuppsats på c-nivå i socialpsykologi utförd vid Högskolan i Skövde. Datamaterialet har tillgängliggjorts med godkännande av handledare Bo Eriksson Göteborgs universitet.

Undersökningen är utförd i samarbete med Länspolismyndigheten i Skaraborg och Skaraborgs landsting, och syftar till att fungera som underlag för polisen i dess arbete att minska brottsligheten och öka tryggheten i projektet "Allas vårt ansvar". Teoretiskt vilar uppsatsen på de socialpsykologiska teorierna om sociala representationer och Thomas-teoremet. En postenkät har skickats till 6000 skaraborgare boende inom länet, fördelat på 400 per kommun. Datamaterialet innehållet bland annat uppgifter om upplevd trygghet i kommunen, åtgärder för att öka den personliga säkerheten, upplevda brott och upplevd trygghet för polisen.

Syfte:

Syftet med studien är ge en bild av människors trygghetsnivå och en uppfattning om vad som påverkar trygghetsnivån samt att fungera som underlag för polisens praktiska arbete.
Trygghetsmätning i Skaraborg 1998
Keywords: crime prevention; brottsförebyggande arbete; crimes against persons; brott mot individer; crimes against property; egendomsbrott; criminals; kriminell; criminal investigation; brottsutredning; delinquency; brottslighet; social psychology; socialpsykologi; behavioural sciences; beteendevetenskap; fear of crime; rädsla för kriminalitet; burglary; inbrott; safety and security; säkerhet och trygghet; safety measures; säkerhetsåtgärder; crime and security; brott; Crime and law enforcement; Kriminalitet och rättstillämpning; Social behaviour and attitudes; Socialt beteende och attityder; Social Sciences; Samhällsvetenskap; Sociology (Excluding Social Work, Social Anthropology, Demography and Criminology); Sociologi (exklusive socialt arbete, socialantropologi, demografi och kriminologi)